The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.20945/2359-3997000000099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inflammatory markers, glycated hemoglobin and placental weight on fetal outcomes in women with gestational diabetes

Abstract: Objective: The aim of this study was to evaluate the relationship between inflammatory cytokines, placental weight, glycated hemoglobin and adverse perinatal outcomes (APOs) in women with gestational diabetes mellitus (GDM). Subjects and methods: This was a prospective, longitudinal and observational study conducted from April 2004 to November 2005 in Bauru, Brazil. Included patients had singleton pregnancies and performed a 100 g OGTT and had the levels of C-reactive protein (CRP), interleukin (IL)-6, TNF alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Across the KQs reported in this manuscript, a total of 76 studies were included (18 RCTs [different screening strategies, n = 27 196; treatment benefits and harms, n = 4045], 2 nonrandomized controlled intervention studies of treatment [n = 190], and 56 observational studies [screening benefits, n = 4336; screening harms, n = 166 082; diagnostic accuracy, n = 91 260]) (Figure 2). Twenty-three studies were carried over from the prior USPSTF review and 52 new studies were added.…”
Section: Resultsmentioning
confidence: 99%
“…Across the KQs reported in this manuscript, a total of 76 studies were included (18 RCTs [different screening strategies, n = 27 196; treatment benefits and harms, n = 4045], 2 nonrandomized controlled intervention studies of treatment [n = 190], and 56 observational studies [screening benefits, n = 4336; screening harms, n = 166 082; diagnostic accuracy, n = 91 260]) (Figure 2). Twenty-three studies were carried over from the prior USPSTF review and 52 new studies were added.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed an association between high levels of IL-6 and GDM [105][106][107]; however, these studies were limited by the gestational age at which IL-6 levels were measured, the population assessed, and by controlling for confounders such as BMI. Other studies failed to demonstrate a difference in IL-6 levels between GDM and normal pregnancies [108,109]. Nevertheless, a study by Hassiakos et al showed that first-trimester IL-6 levels were a significant predictor of GDM development later in pregnancy and adding IL-6 to a prediction model that included maternal characteristics yielded an improved prediction [110].…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…Numerous studies have been conducted on the association of IL-6 with GDM. Some studies have shown a statistically significant association between elevated IL-6 levels and GDM [ 4 , 13 , 16 ], while others did not report such relationships [ 17 , 18 ]. To this end, considering the contradictory results regarding the association between IL-6 and GDM, and based on the literature, there is no systematic review discussing the association between IL-6 and GDM.…”
Section: Introductionmentioning
confidence: 99%